Occurence of Culturable Vibrio cholerae from Lake Victoria, and Rift Valley Lakes Albert and George, Uganda - Kaddumukasa, Martha; Nsubuga, David; Muyodi, Fredrick J. (Lakes & Reservoirs: Research & Management, 2012)
Vibrio cholerae, a bacterium that causes cholera, poses a human health risk when consumed via untreated or contaminated water. Monthly investigations into the presence of V. cholerae from Lakes Albert, George and Victoria were conducted, with the goal being to examine the relationship between the occurrences of V. cholerae with various water quality parameters at fish landing sites in major water bodies in Uganda. The pH, temperature and electrical conductivity were measured at three fishing sites in each of the three study lakes; namely Gabba in Lake Victoria, Butiaba in Lake Albert and Kayanzi in Lake George. The pH values varied from 7.76 to 9.36 at Butiaba, 8.68 to 9.85 at Kayanzi and 6.6 to 9.88 at Ggaba. The temperature ranged from 17.9 to 32.3 C at Butiaba, 22.5 to 29 C at Kayanzi and 18.2 to 30.5 C at Ggaba. The electrical conductivity ranged from 129.2 to 984 lS cm)1 at Butiaba, 658 to 1090 lS cm)1 at Kayanzi and 119 to 218 lS cm)1 at Ggaba, for Lakes Albert, George and Victoria, respectively. Enrichment techniques were used to detect culturable V. cholerae on TCBS culture media. Seventy-five (75%) of the samples (n = 90) were positive for V. cholera. The occurrence of V. cholerae was positively associated with water quality parameters over the 10-month period of study. Vibrio cholerae was more frequently detected during the dry season (warmer) than during the wet season. These study results suggest the investigated study lakes are natural reservoirs for V. cholerae.
Keywords: George and Victoria; Rift valley; Lakes Albert; Uganda; Vibrio cholerae; Waterborne diseases